« Absence, ténèbres, silence et poussière ». La scénographie d’outre-tombe dans les Mémoires d’Alexandre de Tilly - Katrien Horemans (Contextes)
This article aims to gain an understanding of the manifestation of life writing in France at the turn of the Enlightenment, and more specifically of the discursive features and culturally anchored assumptions it exhibits with regard to autobiographical narration. To this purpose, a discursive study of the Memoirs (1828) of the count Alexandre de Tilly (1764-1816) will be carried out. In particular, I propose to examine whether the ‘scenography’ of death and the ethos of trustworthiness that results from the former could have functioned as a discursive strategy that served both the purposes of accreditation and legitimation of autobiographical writings. The initial hypothesis is that all those who strived to unveil their private lives to the eyes of the public in the French (pre)modern period had to negotiate their appearance on the public stage in order to circumvent an ‘autobiographical taboo’ that weighed heavily on discourses of the self. Hence, the approach taken in this article is pragmatic rather than essentialist and aims to examine to what extent (early) modern autobiography is the result of a process of constant interaction and negotiation with the social, historical and discursive context in which it appears in order to circumvent the sentiment of transgressive unveiling that was entangled with private testimony.